(untitled) (Texas Journal of Engineering and Technology, 2023)
The article discusses the effectiveness of using modern programs in the design of construction structures of buildings and structures. The purpose of this work is to analyze modern software components of BIM technologies. The article presents a mutual comparison of programs for improving the calculation of building structures. These programs allow to reduce the period of development of project documents for the construction of buildings and structures, and also provide a complete set of calculations of various structures that contribute to the efficient work of builder-designers.